Intimal Arteritis and Microvascular Inflammation Are Associated With Inferior Kidney Graft Outcome, Regardless of Donor-Specific Antibodies - Novotny, Marek; Hruba, Petra; Kment, Martin; Voska, Ludek; Kabrtova, Katerina; Slavcev, Antonij; Viklicky, Ondrej (Frontiers in Medicine, 2021)
Background: The prognostic role of intimal arteritis of kidney allografts in donor-specific antibody negative (DSA–) antibody-mediated rejection (ABMR) remains unclear. Methods: Seventy-two out of 881 patients who had undergone kidney transplantation from 2014 to 2017 exhibited intimal arteritis in biopsies performed during the first 12 months. In 26 DSA negative cases, the intimal arteritis was accompanied by tubulointerstitial inflammation as part of T cell-mediated vascular rejection (TCMRV, N = 26); intimal arteritis along with microvascular inflammation occurred in 29 DSA negative (ABMRV/DSA–) and 19 DSA positive cases (ABMRV, DSA+, N = 17). In 60 (83%) patients with intimal arteritis, the surveillance biopsies after antirejection therapy were performed. Hundred and two patients with non-vascular ABMR with DSA (ABMR/DSA+, N = 55) and without DSA (ABMR/DSA–, N = 47) served as controls. Time to transplant glomerulopathy (TG) and graft failure were the study endpoints. Results: Transplant glomerulopathy -free survival at 36 months was 100% in TCMRV, 85% in ABMR/DSA–, 65% in ABMRV/DSA-, 54% in ABMR/DSA+ and 31% in ABMRV/DSA+ (log rank p < 0.001). Death-censored graft survival at 36 months was 98% in ABMR/DSA-, 96% in TCMRV, 86% in ABMRV/DSA–, 79% in ABMR/DSA+, and 64% in ABMRV/DSA+ group (log rank p = 0.001). In surveillance biopsies, the resolution of rejection was found in 19 (90%) TCMRV, 14 (58%) ABMRV/DSA–, and only 4 (27%) ABMRV/DSA+ patients (p = 0.006). In the multivariable model, intimal arteritis as part of ABMR represented a significant risk for TG development (HR 2.1, 95% CI 1.2–3.8; p = 0.012) regardless of DSA status but not for graft failure at 36 months. Conclusions: Intimal arteritis as part of ABMR represented a risk for early development of TG regardless of the presence or absence of DSA. Intimal arteritis in DSA positive ABMR represented the high-risk phenotype.